Pengaruh Budaya Organisasi Terhadap Kinerja Karyawan PT Pasadena Engineering Indonesia - Sri Yanthy Yosepha (Universitas Serang Raya, 2019)
The purpose of this study is to determine how much influence Organizational Culture on Employee Performance PT Pasadena Engineering Indonesia . The method used is quantitative methods and techniques of data collection by questionnaire (questionnaire)PT Pasadena Engineering Indonesia (PEI) is a company engaged in the field of engineering consultancy services, procurement and construction. In PEI still found a discrepancy between the competence of human resources with the duties and responsibilities given the management to the employees , in addition to the culture of the organization placed on PEI are still considered less systematic , so that the mechanism in conducting the process of work is still based on the habits , the consequences arising strong dependence will be a stage of the process .The population is determined as the object of study in this research are all employees of PEI as many as 100 people , and the total sample of 80 respondents The results showed that , Tthere is a positive influence between organizational culture to performance, through the calculations have been done for the t value of 4.369 and 0.000 significance value of less than 0.05 thus Ha accepted and Ho rejected.